Gender in Nepalese Higher Education Curriculum: An Example from Tribhuvan University - Sharma, Hari Maya (The Educator Journal, 2022)
This paper analyses the course entitled 'English Language Teaching (ELT) practices and materials' offered by Tribhuvan University for Master's level in English education from a gender perspective. The main objective of the paper is to explore and analyse gender inequalities underlying in the processing and production of the course. Taking the course documents as the primary source of data, this paper found that the course falls short in gender mainstreaming and has revealed gender-blindness in content selection and recommended/reference materials encouraging gender inequality during the course development process as well as in its production.